Answer:
14x+4
Step-by-step explanation:
5x+5x+2x+2x+3+3-1-1
5x+5x+2x+2x=14x
3+3-1-1=4
14x+4
Answer:
6/21
Step-by-step explanation:
Answer:
1 3/8
Step-by-step explanation:
3 2/3 = 11/3
2 2/3 = 8/3
11/3 / 8/3 = 11/3*3/8 = 11/8 = 1 3/8
The answer is 169 because 180-11=169
Answer:
( x - 2 )^2 + ( y - 1 )^2 = 1
Step-by-step explanation:
As i previously explained,
The general form of equation for a circle is ( x - h )^2 + ( y - k )^2 = r^2.
h and k are the co-ordinates of the center of circle and r is the radius
Here, We have (2,1) as the co-ordinates of the center of circle
Now,
( x - h )^2 + ( y - k )^2 = r^2
or,( x - 2 )^2 + ( y - 1 )^2 = r^2
The radius of the circle is 1 units(from figure)
So, put that in, we get
( x - 2 )^2 + ( y - 1 )^2 = 1^2
or, ( x - 2 )^2 + ( y - 1 )^2 = 1
You can simplify this or leave it here.